Quality and impact of eviQ Cancer Treatments Online (www.eviq.org.au): the medical oncologist's perspective. Issue 2 (25th May 2017) - Loke, Lydia P. Y.; Chen, Tina Y. T.; Lewis, Craig R.; Ward, Robyn L.; Rushton, Shelley A.; Shapiro, Jeremy D.
Abstract: Introduction: eviQ Cancer Treatments Online is a free, web‐based resource providing access to over 600 evidence‐based treatment protocols in medical oncology, radiation oncology, hematology and cancer genetics. With over 60 000 registrants from 148 countries, eviQ is widely used by cancer clinicians globally. The aim of this study was to examine the perceived quality of eviQ by Australian medical oncologists, the impact it had on their knowledge and practice, and the effect it had on their patients. Methods: A web‐based survey was administered to members of the Medical Oncology Group of Australia by email. Two reminders emails were sent to encourage participation. Results: Of the 97 respondents (15%), all but one, were practicing in Australia, with varying years of oncology experience (<2 years: 25%, 2–10 years: 36%, >10 years: 39%). eviQ was most frequently used as a source for providing patient information sheets on chemotherapy side effects, with 57% of respondents using eviQ for this purpose. Other uses included accessing side effect information (27%), checking drug doses (26%) and guiding dose adjustments (22%). The majority of respondents rated eviQ as current, accurate and relevant with over 90% agreeing that eviQ was of a high quality. Most of the respondents reported that they provided better care with enhanced patient experiences as a result of using eviQ. Conclusions: eviQ was highly regarded by Australian medical oncologists who responded to our survey. The results suggested that usage of eviQ had a positive impact on individual knowledge, practice and promoted better patient‐centered care.